The SNARE Complex from Yeast is Partially Unstructured on the Membrane - Su, Zengliu (2008)
Molecular recognition between cognate SNAREs leads to formation of a four-helix bundle, which facilitates vesicle docking and membrane fusion. For a SNARE system involved in trafficking in yeast, target membrane (t-) SNARE Sso1p and vesicle associated (v-) SNARE Snc2p contribute one SNARE motif each, while another t-SNARE Sec9 donates two N-terminal and C-terminal SNARE motifs SN1 and SN2 to the helical bundle. Using EPR it is found that SN2 has a tendency to be uncoiled, leaving a significant population of the SNARE complexes to be partially unstructured on the membrane. In sharp contrast, SN2 is fully engaged in the four-helix bundle when removed from the membrane, showing that the membrane is the main destabilizing factor. Helix-breaking proline mutations in SN2 did not affect the rate of docking but reduced the rate of lipid mixing significantly, indicating that SN2 plays an essential role in activating the transition from docking to fusion.